Diabetic Retinopathy Screening Ratio Is Improved When Using a Digital, Nonmydriatic Fundus Camera Onsite in a Diabetes Outpatient Clinic. (21st January 2016) - Roser, Pia; Kalscheuer, Hannes; Groener, Jan B.; Lehnhoff, Daniel; Klein, Roman; Auffarth, Gerd U.; Nawroth, Peter P.; Schuett, Florian; Rudofsky, Gottfried
Abstract : Objective . To evaluate the effect of onsite screening with a nonmydriatic, digital fundus camera for diabetic retinopathy (DR) at a diabetes outpatient clinic. Research Design and Methods . This cross-sectional study included 502 patients, 112 with type 1 and 390 with type 2 diabetes. Patients attended screenings for microvascular complications, including diabetic nephropathy (DN), diabetic polyneuropathy (DP), and DR. Single-field retinal imaging with a digital, nonmydriatic fundus camera was used to assess DR. Prevalence and incidence of microvascular complications were analyzed and the ratio of newly diagnosed to preexisting complications for all entities was calculated in order to differentiate natural progress from missed DRs. Results . For both types of diabetes, prevalence of DR was 25.0% (n = 126 ) and incidence 6.4% (n = 32 ) (T1DM versus T2DM: prevalence: 35.7% versus 22.1%, incidence 5.4% versus 6.7%). 25.4% of all DRs were newly diagnosed. Furthermore, the ratio of newly diagnosed to preexisting DR was higher than those for DN (p = 0.12 ) and DP (p = 0.03 ) representing at least 13 patients with missed DR. Conclusions . The results indicate that implementing nonmydriatic, digital fundus imaging in a diabetes outpatient clinic can contribute to improved early diagnosis of diabetic retinopathy.